The Role of Perceived Value in Advertising Message on Purchase Intention: A Case of Malaysian Millennial Consumers - Arman Hj. Ahmad; Izian Idris; Gan Hao Rong; Rizal Ula Ananta Fauzi; Nursyuhadah Abdul Rahman; Ridzuan Masri (International Journal of Business and Quality Research, 2024)
This research investigates the perceived value of advertising messages towards Millennials with regards to the extent of perceived informativeness, perceived credibility and perceived entertainment of advertising messages in indicating their behavioural intention. 300 Millennials in Malaysia were conveniently recruited to be involved in the data collection of this research. They were recruited because they are the largest age group that is largely exposed to advertising in Malaysia and they are also potential customers in the future. All collected data were scientifically analysed using SPSS, particularly using the Multiple Linear Regression Analysis to test the relationship between variables and to find out the strengths of each connection of variables. On top of that, the objective of this research is to identify the most significant factor that influences consumers’ purchase intention. Interestingly, the results show evidence of the positive relationship between the perceived value of advertising messages and consumers’ purchase intention which is predicted and supported by various studies. In summary, all of the findings in this research can be summarised as, all of the three variables including perceived informativeness, perceived credibility and perceived entertainment of advertisement messages are positively associated with millennials’ purchase intention in Malaysia. Among the three factors, the perceived entertainment of advertising messages is the most significant driver that influenced Millennials behavioural intention. On top of that, all research objectives and research questions were achieved and answered throughout this study.